Exploring Spray-Coating Techniques for Organic Solar Cell Applications. (14th May 2012) - Nie, Wanyi; Coffin, Robert; Liu, Jiwen; MacNeill, Christopher M.; Li, Yuan; Noftle, Ronald E.; Carroll, David L.
Abstract : We have investigated spray coating as a novel processing method for organic solar cell fabrication. In this work, spraying parameters and organic solvent influences have been correlated with cell performance. Using airbrush fabrication, bulk heterojunction photovoltaic devices based on a new low band gap donor material: poly[(4, 8-bis(1-pentylhexyloxy)benzo[1, 2-b:4, 5-b ′ ]dithiophene-2, 6-diyl-alt-2, 1, 3-benzoxadiazole-4, 7-diyl] with the C60-derivative (6, 6)-phenyl C61-butyric acid methyl ester (PCBM) as an acceptor, have achieved power conversion efficiencies over 3%. We show that airbrush fabrication can be carried out with simple solvents such as pristine 1, 2-dichlorobenzene. Moreover, the influence of device active area has been studied and the 1 cm 2 device by spray coating maintained an excellent power conversion efficiency of 3.02% on average.